The Interpretation of Silent Behaviour in Intercultural Small Talk Situations - Cascarino, Dino (My University, 2002)
This study endeavoured to determine why silent behaviour from Finns during interaction may produce feelings of conflict among some foreigners, and how this tension might be subsequently reduced. Empirical material was collected through a series of recorded interviews with 16 foreign students, who commented on their experiences in communicating with Finns. There was substantial evidence to suggest that conflict had developed as a result of more talkative speakers interpreting silence according to the norms and values within a talkative culture. In other words, speakers had assumed projected similarity. It was found that awareness and appreciation of communication values within silent cultures could result in a reduction in tension, therefore encouraging successful intercultural communication. Furthermore, concepts such as 'intercultural speaker' and 'intercultural politeness' were introduced and discussed.
Keywords: Conversational style; politeness; projected similarity; silence; fi=Englannin kieli|en=English language|